Utilization of Social Media as a Means of Healthy Food Promotion by Housewives in Dumai City - Megawati Megawati; Syafruddin Pohan (PERSPEKTIF, 2022)
The purpose of this study was to analyze the role of social media in promoting healthy food by Hanadona Catering in Dumai City. This study uses a constructivist paradigm with a descriptive qualitative approach. The research subject only involved the owner of Hanadona Catering, namely Mrs. Aldona Wulandari as the main informant. Data collection techniques are through in-depth interviews conducted directly (via the Zoom application) or indirectly (via WhatsApp chat) and non-participant observation. The results of this study indicate that Hanadona Catering uses social media WhatsApp Messenger, Instagram, and Facebook to promote its culinary products. Promotional activities are usually carried out alone, involving the community and using the services of celebgrams and influencers from the local area. The massive promotions carried out have made the existence of Hanadona Catering for the last three years quite well known to the people of Dumai city and economically it brings benefits to the owner and the surrounding community, although on the other hand there are obstacles in terms of the availability of human resources to manage social media if it is overloaded. orders.